A iniciação científica de professores em formação inicial do curso de pedagogia da Universidade do Estado do Amazonas, polo Parintins - Am - Coelho Filho, Mateus de Souza (2012)
We investigated as to how happens Undergraduate Research in the investigative process of teachers in initial training of the Education Course (4th, 6th and 7th periods), they do Undergraduate Research through the Support Program for Undergraduate Research (PAIC) funded by Foundation for Research in Amazonas state-FAPEAM, specifically at the Center for Advanced Studies in Parintins, Unity State University of Amazonas in the city of Parintins-Am in the Baixo Amazonas region. Tariff in the qualitative perspective, relying on the phenomenological approach and aided by technical interview. The record of the investigative experiences of teachers in initial training pointed to the understanding of Undergraduate Research as an articulator of the process of science education as it allows teachers a practical contact with scientific activity, enabling the engagement in the world of investigation and scientific research, allowing a close relationship with the world of knowledge and assumptions derived from science. It was found that undergraduate research is an extremely important element in the training of undergraduates investigated since enabled knowledge able to insert them in the research world, the world of science and the investigative world.